The Influence of International Auditing Standards on the Performance of Government Auditors in Indonesia - Pani Gunawan Pratama; Renny Maisyarah (CV. ADMITECH SOLUTIONS, 2025)
This study aims to determine the effect of independence, professionalism, and professional ethics of auditors on the performance of auditors in public accounting firms in South Surabaya. The sampling method in this study used purposive sampling method, and data collection techniques used survey methods by distributing questionnaires to the public accounting firm in Surabaya, with a total of 100 questionnaires and 40 questionnaires that could be processed. The data analysis method used is multiple linear regression analysis. The results of this study indicate that the independence, professionalism, and professional ethics of auditors have a positive effect on the performance of auditors. Auditors need to develop their knowledge on an ongoing basis by implementing formal education programs and professional training related to the duties of auditors, and an increase in auditor performance is also absolutely necessary because considering that professional accounting services are increasingly needed. This shows that the higher the level of independence, professionalism, and professional ethics of auditors, the higher the performance of auditors in public accounting firms in Surabaya